Moderate intense physical activity depends on selected Metabolic Equivalent of Task (MET) cut-off and type of data analysis. - Hans van Remoortel (Public Library of Science (PLoS), 2013)
Background Accelerometry data are frequently analyzed without considering whether moderate-to-vigorous physical activities (MVPA) were performed in bouts of >10 minutes as defined in most physical activity guidelines. We aimed i) to quantify MVPA by using different commonly-applied physical activity guidelines, ii) to investigate the effect of bouts versus non-bouts analysis, and iii) to propose and validate a MVPA non-bouts cut-point to classify (in-) active subjects. Methods Healthy subjects (n=110;62±6yrs) and patients with Chronic Obstructive Pulmonary Disease (COPD) (n=113;62±5yrs) wore an activity monitor for 7 days. Three Metabolic Equivalent of Task (MET) cut-offs and one individual target (50% VO₂ reserve) were used to define MVPA. First, all minutes of MVPA were summed up (NON-BOUTS). Secondly, only minutes performed in bouts of >10 minutes continuous activity were counted (BOUTS). Receiver operating characteristic (ROC) curve analyses were used to propose and (cross-) validate new MVPA non-bout cut-points based on the criterion of 30 minutes MVPA per day (BOUTS). Likelihood ratios (sensitivity/[1-specificity]) were used to express the association between the proposed MVPA non-bout target and the MVPA bout target of 30 min*day⁻¹. Results MVPA was variable across physical activity guidelines with lowest values for age-specific cut-offs. Selecting a METs cut-point corresponding to 50% VO₂ reserve revealed no differences in MVPA between groups. MVPA's analyzed in BOUTS in healthy subjects were 2 to 4 fold lower than NON-BOUTS analyses and this was even 3 to 12 fold lower in COPD. The MVPA non-bouts cut-point of 80 min*day⁻¹ using a 3 METs MVPA threshold delivered positive likelihood ratios of 5.1[1.5-19.6] (healthy subjects) and 2.3[1.6-3.3] (COPD). Conclusion MVPA varies upon the selected physical activity guideline/targets and bouts versus non-bouts analysis. Accelerometry measured MVPA non-bouts target of 80 min*day⁻¹, using a 3 METs MVPA threshold, is associated to the commonly-used MVPA bout target of 30 min*day⁻¹.